2015
DOI: 10.4238/2015.october.19.13
|View full text |Cite
|
Sign up to set email alerts
|

Induction and identification of Stylosanthes guianensis tetraploids

Abstract: ABSTRACT. Stylosanthes guianensis is an elite and important forage legume species, which is extensively cultivated in tropical areas. Polyploid breeding via exposure to colchicine is a conventional and practical method to improve varieties of S. guianensis. Terminal buds of S. guianensis Reyan No.5 seedlings were treated with different concentrations of colchicine (0.00, 0.05, 0.10, 0.15, 0.20, and 0.25%) for 24, 48, and 72 h. Morphological and cytological variants were observed at a frequency of <96% among tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
1
1
0
1
Order By: Relevance
“…This research found that P. Ox Black Face Ox 1647 had the highest number of orchid buds compared to the other two orchid varieties (Table 1). A similar study by [18] showed colchicine treatment on young shoots of Lilium flowers of the Con. Amore variety with a concentration of 2,000 ppm caused 81.3% flower loss.…”
Section: Quantitative Characteristics Of Flowersupporting
confidence: 52%
“…This research found that P. Ox Black Face Ox 1647 had the highest number of orchid buds compared to the other two orchid varieties (Table 1). A similar study by [18] showed colchicine treatment on young shoots of Lilium flowers of the Con. Amore variety with a concentration of 2,000 ppm caused 81.3% flower loss.…”
Section: Quantitative Characteristics Of Flowersupporting
confidence: 52%
“…The basic chromosome number of the hyacinth cultivar was eight, and the numbers of chromosomes in the diploid, triploid, tetraploid, and aneuploid cultivars were 16, 23, 24, 31, and 32, respectively. In a similar study, Wu et al (2015) studied the induction and identification of Stylosanthes guianensis tetraploids. Souza et al (2015) observed the genetic alteration and meiotic behavior of Brachiaria decumbens hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…Tanaman stylo (Stylosanthes guianensis) adalah tanaman leguminosa asli dari Amerika Selatan dan Tengah (Wu et al 2015) yang memiliki tinggi berkisar 0,6 m-1,2 m dengan diameter batangnya 0,3 cm-0,8cm (Jiang et al 2017) panjang daun mencapai 6 cm, memiliki kandungan protein kasar yang cukup tinggi jika dibandingkan dengan rumput yaitu berkisar pada 16%-17%, kandungan bahan kering 15%-23% serta produksi biomassa pertahunnya mencapai 40 ton ha -1 berdasarkan bahan kering (Litbang Pertanian,2012;Yulia et al 2022). Stylo merupakan salah satu tanaman leguminosa yang sudah banyak dimanfaatkan sebagai pakan ternak karena memiliki daya adaptasi yang bagus khususnya pada kondisi asam.…”
Section: Pendahuluanunclassified